Análise molecular, características morfológicas e reações de cultivares de soja à Phytophthora sojae - Bordon, Caroline de Marchi (2013)
Soybean (Glycine max. (L.) Merr.) belongs to Fabaceae family originated from east coast of Asia. It was introduced in Brazil in 1882, becoming currently one of the major agricultural products of the Country. The cultivation of soybean led the country to a prominent position in global agribusiness, making it a major producer and exporter of grain and byproducts. Phytophthora rot in soybean can affect the crop at any stage of development, causing symptoms of rot seeds, tipping, root and stem rot. Their development is favored by conditions of clay soils, compacted and subjected to prolonged periods of moisture saturation. The occurrence of the disease has been reported in several soybean producing regions in the world which resulted in large productivity losses and economic damage to farmers. The main causal agent of the disease was recognized as Phytophthora sojae, despite reports of other species involved in the pathosystem in countries like United States and China. Pathogen's population has high pathogenic variability showing the existence of many pathotypes. The main tool to control the disease is genetic resistance that use soybean cultivars with resistance genes (Rps) against the pathogen. The objective of the study was to gather a collection of brazilian P. sojae isolates; to make a molecular analysis regarding its identification, to make a morphological characterization of their structures; and evaluate the commercial soybean cultivars reactions recommended for the South Brazil in crop year 2012/2013, for the isolates. Therefore, 10 isolates originated from Paraná and Rio Grande do Sul State were evaluate. The molecular analysis for identification was made by PCR technique with specific primers (PSOJF1 and PSOJR1) developed on the ITS region from pathogen ribosomal DNA and it was obtained specie confirmation of P. sojae for all. The morphological patterns observed were the same described for the P. sojae species, consisting of sporangia persistent; predominantly ovoid, not papillate, with sizes ranging from 34.9 to 56.6 x 24.7 to 33.2 μm. The antherides were predominantly anfigenous and oospores ranged from 17.1 to 39.1 μm in diameter. The pathogenicity analysis showed high variability to 36 commercial cultivars with resistant, intermediate and susceptible reactions. The BRS 282 was susceptible to all isolates, unlike cultivar CD 230, TMA 7161, SD 688, SD 615 RR, BMX and SD 60A02i were resistant to all. The others cultivars had one intermediate or susceptible response for at least one isolate evaluated. Isolates from Paraná, PS 9.1, PS 24.1 and P. S 15.2 were responsible for infecting the largest number of cultivars among those evaluated.